Factors Influencing Impulsive Buying Behaviour Among Generation Z Tiktok Users in Jakarta - Alyaa, Azira Faiza; Hatta, Holila; widyastuti,, Dominica Arni (Journal of Entrepreneurship, Management and Industry (JEMI), 2024)
This study explores the factors that drive impulsive buying behavior among Generation Z TikTok users in Jakarta. We focused on five key aspects: Entertainment, Interaction, Trendiness, Customization, and Word of Mouth, examining how each influences the tendency to make spontaneous purchases. Using a quantitative approach, we gathered data through online questionnaires, targeting Gen Z individuals born between 1997 and 2012 who are active on TikTok. Our sample comprised 200 respondents, carefully selected to provide relevant insights. The analysis was conducted using multinomial logistic regression to understand the strength and significance of each factor's impact. Our findings reveal important insights for marketers looking to harness the power of TikTok to influence young consumers' purchasing decisions. This research highlights the critical role of engaging content, social interactions, and personalized experiences in driving impulsive buying behavior on social media platforms.